1999
DOI: 10.1093/jmedent/36.2.216
|View full text |Cite
|
Sign up to set email alerts
|

Infection of Ixodes ricinus (Acari: Ixodidae) by Borrelia burgdorferi sensu lato in North Africa

Abstract: Free-living adult Ixodes ricinus L. were collected in Amdoun, situated in the Kroumiry mountains in northwestern Tunisia (North Africa). Using direct ßuorescence antibody assay, the infection rate of Þeld-collected I. ricinus by Borrelia burgdorferi sensu lato was 30.5% (n ϭ 72). No difference in infection rate was observed between male and female ticks. Spirochetes that had been isolated from I. ricinus from Ain Drahim (Kroumiry Mountains) in 1988 were identiÞed as Borrelia lusitaniae (formerly genospecies Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 25 publications
1
22
0
2
Order By: Relevance
“…However, in a study in Portugal, B. lusitaniae was the sole B. burgdorferi sensu lato species observed in I. ricinus ticks (6). Similarly, it is by far the most predominant species isolated from ticks in North Africa (35,44,46). A large diversity of the small rrf-rrl spacer was reported among the Portuguese strains (6).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in a study in Portugal, B. lusitaniae was the sole B. burgdorferi sensu lato species observed in I. ricinus ticks (6). Similarly, it is by far the most predominant species isolated from ticks in North Africa (35,44,46). A large diversity of the small rrf-rrl spacer was reported among the Portuguese strains (6).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, these studies suggested a higher diversity among B. lusitaniae around the Mediterranean basin. However, all these studies only focused on the small ribosomal rrf-rrl spacer and, therefore, the global diversity of this species remained unknown.Recently, we reported that B. lusitaniae was, by far, the most prevalent species, ranging from 96.6 to 100% of the B. burgdorferi sensu lato species identified in Tunisia and Morocco (35,44,46). The report of some Lyme borreliosis cases in North Africa (1, 27) and the recent isolation in Portugal of B.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They are B. garinii, B. afzelii, B. valaisiana, and B. lusitaniae (1,6,7). The last, which was isolated from ticks for the first time in 1993 (in Portugal) (10), appears to circulate mainly around the western Mediterranean basin (1,3,6,7,14). To date, the reservoir of B. lusitaniae has not been defined, and little is known about the ecology of this genospecies.…”
mentioning
confidence: 99%
“…lusitaniae has been cultured from Ixodes ricinus and detected by PCR ampli®cation in Hyalomma marginatum ticks in Portugal [5±7], Tunisia [8], Spain [9], Moldavia, the Ukraine and the Czech Republic [10] and Slovakia [11]. Based on comparative RFLP and sequence analysis of the rrf±rrl intergenic spacer region, B. lusitaniae, speci®cally subspecies PotiB1, PotiB2 and PotiB3, form a clade distinct from other northern European isolates of Borrelia spp.…”
Section: Introductionmentioning
confidence: 99%